(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This type of sale has become very common in our time, and the various commodities are represented by the interests in it for both parties to the contract (the seller and the buyer) and when the delay of the price from the date of payment is accompanied by an increase in the price in compensation to the seller for the delay, this type of sale has sparked and is still raised Discussion of controversy among the people of knowledge in terms of its legitimacy because of the increase in the price, perhaps due to what some people suspected of usury.